Genetic variation in leptin and leptin receptor genes is a risk factor for idiopathic recurrent spontaneous abortion - Müller, Andrijana (Croat Med J, 2016)
AIM: To determine whether maternal leptin (LEP) and leptin receptor (LEPR) gene polymorphisms are associated with idiopathic recurrent spontaneous abortion (IRSA). METHODS: This case-control association study conducted from 2010 to 2012 at the Department of Gynecology and Obstetrics, University Hospital Center Osijek and Clinical Institute of Medical Genetics Ljubljana included 178 women with a history of three or more IRSAs before the 22nd week of gestation and 145 women with at least two live births and no history of pathologic pregnancies during reproductive period. Polymorphisms of maternal LEP (rs7799039, rs2122627, rs11761556, rs10244329) and LEPR (rs1137101, rs7516341, rs1186403, rs12062820) were assessed by allele specific real-time polymerase chain reaction. Genotype distribution, allele frequencies, and frequency of haplotypes at LEP and LEPR genetic loci were determined. RESULTS: We observed more frequent genotype for rs7516341 (nominal P = 0.034, odds ratio [OR] 0.61, 95% confidence interval [CI] 0.38-0.97) and rs1137101 (nominal P = 0.048, OR 1.66, 95% CI 1.00-2.80) in the LEPR gene in patients than in controls, but these results did not remain significant after correction for multiple testing according to Bonferroni (adjusted P value threshold was set at 0.05). We did not observe differential distribution of genotype frequencies in the LEP gene between cases and controls. In patients with IRSA, GTCC haplotype in the LEPR gene locus was significantly less frequent than in controls (P = 0.00865, OR 0.45), contrary to ACTC haplotype (P = 0.0087, OR 1.98). CONCLUSIONS: We showed that genetic variability in the LEPR gene was associated with IRSA, warranting confirmation on a greater number of patients and pathogenesis investigation.